Malignant peritoneal mesothelioma associated with abdominal atypical tuberculosis. - Cefrorella, Nora; López Susviela, Julio; Viola Alles, Alberto (Cirugía del Uruguay, 1984)
Analysis of a case of malignan! peritoneal mesothelioma associtated with atypical tuberculosis. There are present atypical mycobacteria (variety Vaccae) that being opportunistic infect under deficient general and/or local conditions. Emphasis is laid on the fact that the peritoneal mesothelioma is a rare occurrence, its diagnosis being generally made by an exploratory laparotomy. With early diagnosis, !he tratment is complete exeresis, ali other measures are only palliative.